Understanding the behavioral determinants of adolescents’ water consumption: A cross-country comparative study - Saskia C.M. Franken; Crystal R. Smit; Rebecca N.H. de Leeuw; Thabo J. van Woudenberg; William J. Burk; Kirsten E. Bevelander; Moniek Buijzen (Dialogues in Health, 2023)
Substituting the consumption of sugar-sweetened beverages (SSB) with that of water can have a positive effect on adolescents’ health. However, despite the attention on this topic in the Global North, it is relatively understudied in other regions of the world, such as the Caribbean. To guide the development of future interventions, understanding the factors determining water consumption among Caribbean adolescents is important. This study examined the behavioral determinants of water consumption among adolescents in Aruba (the Caribbean) and compared them to those in the Netherlands (Western Europe). We used a theoretical model that integrates the dominant theoretical perspectives in the field of public health, including theories of planned behavior, social norms, and intrinsic motivation. This cross-country study included 1,584 adolescents from Aruba and the Netherlands (52% girls; M = 12.34 years; SD = 2.14). The data were analyzed using regression analyses. This study found that in Aruba, adolescents with higher scores of intrinsic motivation, friends’ descriptive norms, attitudes, and behavioral control regarding water consumption drank more water. Moreover, the associations between water consumption and both intrinsic motivation as well as friends’ descriptive norms for adolescents in Aruba were stronger than those found in the Netherlands. These associations imply that it is even more important for Aruban adolescents than Dutch adolescents to be intrinsically motivated or to perceive their friends often consuming water to drink more water. The cross-country comparison implies that future interventions in Aruba aimed at increasing adolescents’ water consumption as an alternative to SSB should focus on enhancing their intrinsic motivation while considering their friends’ social norms.